IgG4-related autoimmune hepatitis: A case report - Yunpeng Li; Lifeng Wang (Journal of International Medical Research, 2023)
IgG-4-related autoimmune hepatitis (IgG4-AIH) is a rare disease. We report here a case of IgG4-AIH in an elderly male patient who was admitted to hospital because of unexplained hepatic insufficiency. After excluding viral hepatitis, alcoholic liver disease, drug-induced liver disease, parasitic infection, hepatolenticular degeneration and other diseases, and observing elevated levels of IgG-4, humoral immunity index, abnormal liver disease antibody spectrum and liver biopsy results, we made a diagnosis of IgG4-AIH. Following treatment with prednisone and ursodeoxycholic acid, the patient's liver function improved significantly and the patient was discharged from hospital.